Titanium superoxide: a heterogeneous catalyst for anti-Markovnikov aminobromination of olefins - Shaikh, Tanveer Mahamadali; Karabal, Pratibha U.; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron Letters, 2009)
A new facile procedure for the aminobromination of olefins in high yields has been described using p-toluene sulfonamide (p-TsNH(2)) and N-bromosuccinimide (NBS) as introgen and bromine sources, respectively, and titanium superoxide as a truly heterogeneous catalyst. The formation of anti-Markovnikov product exclusively in all the cases studied possibly proceeding I free radical reaction pathway is remarkable. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: anti-Markovnikov addition; Bromoamination; N-Bromosuccinimide; p-Toluenesulfonamide; Titanium superoxide

Triethyl phosphite/benzoyl peroxide mediated reductive dealkylation of O-benzoylhydroxylamines: a cascade synthesis of secondary amides - Aegurla, Balakrishna; Mandle, Ram D.; Shinde, Prasad G.; Parit, Ratan S.; Kamble, Sanjay P.; Sudalai, Arumugam; Senthilkumar, Beeran (European Journal of Organic Chemistry, 2020)
A new triethyl phosphite/benzoyl peroxide (BPO) mediated system has been developed for the synthesis of secondary amides with good to excellent yields in a single step. This unprecedented cascade process involves sequential reduction of N-O bond and benzoylation followed by dealkylation of N-C bond ofO-benzoylhydroxylamines (O-BHA). The methodology is versatile as it tolerates a variety of aromatic and aliphaticO-BHA as substrates to access secondary amides.
Keywords: Amides; Cascade reactions; O-Benzoylhydroxylamines; Redox reactions; synthetic methods